ASUHAN KEPERAWATAN PADA PASIEN BRPN DENGAN GANGGUAN PEMENUHAN KEBUTUHAN OKSIGENASI DI RUANG CEMPAKA RSUD dr. GOETENG TAROENA ADIBRATA - Dina Rosmala Silviani; Ikit Netra Wirakhmi (Jurnal Inovasi Penelitian, 2023)
The incidence of bronchopneumonia in developing countries including Indonesia is almost 30% in children under 5 years of age with a high risk of death. Bronchopneumonia or pneumonia is the main cause of death in children worldwide with a total of up to 70% of deaths in the world. bronchopneumonia treated by oxygenation. The basic need for oxygenation is the most vital basic need in human life. This is related to the process of cell metabolism, where this process requires oxygen in the body. If there is a lack of oxygen, it can have a significant impact on the body. Goeteng Taroena Adibrata The research design is descriptive through case studies in patients with basic needs for oxygenation with a medical diagnosis of bronchopneumonia. The population is all patients who experience bronchopneumonia with a sample of 1 respondent. Data collection was carried out by means of anamnesis, observation, physical examination, and documentation study. Data analysis by validating the results of the study with the IDHS to draw conclusions about the nursing problems that arose in the respondents. The results of this study are that coughing and shortness of breath in children have been reduced by being given nebulizer therapy with decreased sputum production specifications, improved breathing patterns and improved respiratory frequency